Venture Capital Financing: Perspective of Entrepreneurs in an Emerging Economy - Adusei, Charles; Isaac, Tweneboah-Koduah (Archives of Business Research, 2017)
In the developing countries the need for capital of small businesses remains small and fragmented despite a vast number of small businesses operating in these countries. A cross-sectional survey of entrepreneurs was conducted within the Kumasi Metropolis of Ghana on their perspective of venture capital financing. Questionnaires were used to assess their perception and impact of venture capital financing on small businesses whiles descriptive statistics and multiple linear regression were used to analyse the data. Result revealed that the requirement for accessing venture capital was difficult and cumbersome but the entrepreneurs confirmed that venture capital financing and its related packages can make the enterprise a success. The study found sales, innovation and efficiency variables to be positively significant whiles profit has a negative significant impact on venture growth and performance. This study suggests that the venture capital trust fund must embark on nationwide educational drive by engaging the business communities on its operations. The government must show real commitments and programmes towards the realisation of private enterprises development. Furthermore, the study prescribed five generic requirements for entrepreneurs and the venture capital industry that will guide start-up businesses.